The Irish tradition in Old English literature - Wright, Charles Darwin 1954- (Cambridge studies in Anglo-Saxon England, 1993)
Irish monks and missionaries played a crucial role in the conversion of the pagan Anglo-Saxons and in the formation of Christian culture in England, but the nature and extent of Irish influence on Old English poetry has remained largely undefined. Charles Wright identifies the characteristic features of Irish Christian literature which influenced Anglo-Saxon vernacular authors. Professor Wright traces the Irish background of the distinctive contents of Vercelli Homily IX and its remarkable exemplum, 'The Devil's Account of the Next World', and traces the dissemination of related stylistic and thematic material elsewhere in Old English literature, including other anonymous homilies such as Beowulf and the Solomon and Saturn texts. As a full-length study of Irish influence on Old English religious literature, the book will appeal to scholars in Old English literature, Anglo-Saxon studies, and Old and Middle Irish literature